Artificial intelligence in sport performance analysis - Araújo, D.; Couceiro, M. S.; Seifert, L.; Sarmento, H.; Davids, K. (Routledge, 2021)
To understand the dynamic patterns of behaviours and interactions between athletes that characterize successful performance in different sports is an important challenge for all sport practitioners. This book guides the reader in understanding how an ecological dynamics framework for use of artificial intelligence (AI) can be implemented to interpret sport performance and the design of practice contexts.